2011
DOI: 10.1186/1748-717x-6-174
|View full text |Cite
|
Sign up to set email alerts
|

Can the risk of secondary cancer induction after breast conserving therapy be reduced using intraoperative radiotherapy (IORT) with low-energy x-rays?

Abstract: BackgroundRadiation induced secondary cancers are a rare but severe late effect after breast conserving therapy. Intraoperative radiotherapy (IORT) is increasingly used during breast conserving surgery. The purpose of this analysis was to estimate secondary cancer risks after IORT compared to other modalities of breast radiotherapy (APBI - accelerated partial breast irradiation, EBRT - external beam radiotherapy).MethodsComputer-tomography scans of an anthropomorphic phantom were acquired with an INTRABEAM IOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…This allows for adjustments in applicator placement as well as the collection of information regarding projected dose to adjacent organs and structures, including the skin, chest wall, and heart . HDR is known to increase the risk of secondary malignancies following breast irradiation, including lung, bone, and soft tissue tumours . In addition, radiation exposure has been shown to cause myocardial fibrosis and the potentiation of coronary artery disease .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows for adjustments in applicator placement as well as the collection of information regarding projected dose to adjacent organs and structures, including the skin, chest wall, and heart . HDR is known to increase the risk of secondary malignancies following breast irradiation, including lung, bone, and soft tissue tumours . In addition, radiation exposure has been shown to cause myocardial fibrosis and the potentiation of coronary artery disease .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiation exposure has been shown to cause myocardial fibrosis and the potentiation of coronary artery disease . The maximum radiation doses received by the heart, lungs, and skin are consistently lower for IORT than for external beam whole breast radiation, and thus associated with a lower estimated risk for radiation‐associated damage or oncogenesis . The additional ability for PB‐IORT to allow for alteration of the regular spheroid dose shape to adjust away from the skin and chest wall suggests its capacity to further decrease the radiation dose – and potential deleterious effects – delivered to these structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of SPC induction was estimated using the NCRP report 116 for treatment plans generated on an anthropomorphic phantom. The study reported a reduced risk estimate associated with IORT and mammosite, compared to EBRT [6].…”
mentioning
confidence: 95%
“…myocardial infarction, coronary revascularization, or death from ischemic heart disease) based on dosage exposure to radiation [ 6 , 7 ]. Additionally, the risk of second solid cancers after radiotherapy for breast cancer is also increased [ 8 , 9 ]. These events not only increase the direct costs in treating these patients over their entire life but as well affect their overall quality of life [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%